Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Prerequisites - p.4 - Factoring Polynomials - Exercises - Page 39: 61



Work Step by Step

Use: $4x=3x+x$ and $-4x=-3x-x$ $(x^2+3)^2-16x^2=(x^2+3)^2-(4x)^2=(x^2+3+4x)(x^2+3-4x)=(x^2+3x+x+3)(x^2-3x-x+3)=[x(x+3)+1(x+3)][x(x-3)-1(x-3)]=(x+1)(x+3)(x-1)(x-3)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.